Building a conceptual architecture and stakeholder map of a system-of-systems for disaster monitoring and early-warning: A case study in Brazil - Horita, Flávio E. A.; Rhodes, Donna H.; Inocêncio, Thiago J.; Gonzales, Gustavo R. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
Monitoring systems are essential for prompt action in case of a disaster, as well as for understanding these systems as constituent systems within a System-of-Systems (SoS) can provide new and unique features that cannot be provided by any individual system separately. Furthermore, the identification of existing stakeholders also plays an important role, as constituent systems may be associated with multiple requirements. Therefore, this work presents two artifacts -a conceptual architecture and a stakeholder map - of a SoS for disaster monitoring and early-warning. A Design Science Research (DSR) within a Brazilian early-warning center has been conducted for designing and evaluating the artifacts. An artifact generalization approach has been also employed for generalizing the artifacts from a specific to a broader and generic scenario. Study findings showed that a SoS for disaster monitoring and early-warning should comprise nine constituents, which are used by four groups of stakeholders.